2018
DOI: 10.1371/journal.pone.0202822
|View full text |Cite
|
Sign up to set email alerts
|

Calcium imaging of CPG-evoked activity in efferent neurons of the stick insect

Abstract: The stick insect is a well-established experimental animal to study the neural basis of walking. Here, we introduce a preparation that allows combining calcium imaging in efferent neurons with electrophysiological recordings of motor neuron activity in the stick insect thoracic nerve cord. The intracellular free calcium concentration in middle leg retractor coxae motor neurons and modulatory octopaminergic DUM neurons was monitored after backfilling lateral nerve nl5 that contains the axons of these neurons wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…5). These data resemble the effects of the muscarinic agonist pilocarpine in deafferented insect VNC preparations, which generate rhythmic activity of alternating motor neuron pools controlling joint movement (Baudoux et al, 1998; Chrachri and Clarac, 1987; David et al, 2016; Goldammer et al, 2018; Rillich et al, 2013; Ryckebusch and Laurent, 1993). Moreover, this rhythmic activity is independent within the three leg joints, as these rarely exhibit coordinated activity between them, meaning that different CPGs control the antagonistic activity of motor neuron pools of each leg joint (Bidaye et al, 2018; Büschges et al, 1995; Daun et al, 2019; Ryckebusch and Laurent, 1994).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…5). These data resemble the effects of the muscarinic agonist pilocarpine in deafferented insect VNC preparations, which generate rhythmic activity of alternating motor neuron pools controlling joint movement (Baudoux et al, 1998; Chrachri and Clarac, 1987; David et al, 2016; Goldammer et al, 2018; Rillich et al, 2013; Ryckebusch and Laurent, 1993). Moreover, this rhythmic activity is independent within the three leg joints, as these rarely exhibit coordinated activity between them, meaning that different CPGs control the antagonistic activity of motor neuron pools of each leg joint (Bidaye et al, 2018; Büschges et al, 1995; Daun et al, 2019; Ryckebusch and Laurent, 1994).…”
Section: Discussionsupporting
confidence: 56%
“…These results are similar to the pharmacological stimulation of decapitated flies with stimulatory amines, notably serotonin, dopamine, and octopamine, which lead to locomotor bouts (Yellman et al, 1997). Moreover, studies in deafferented VNCs using the muscarinic cholinergic agonist pilocarpine, have shown alternating and rhythmic activity in antagonistic leg motor neuron pools driven by the CPGs (Bidaye et al, 2018; Büschges et al, 1995; David et al, 2016; Fuchs et al, 2011; Goldammer et al, 2018; Pearson, 1972; Ryckebusch and Laurent, 1993). Despite this large body of work, the identity, location and architecture of the CPG population remains largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…For the stick insect, it was shown that transection along the ganglionic midline does not impair the pharmacologically induced rhythmicity, implying the existence of hemisegmental CPGs (Büschges et al, 1995). Calcium oscillations accompany the CPG‐driven activity in leg motor neuron pools (Baden & Hedwig, 2009; Goldammer, Mantziaris, Büschges, & Schmidt, 2018), indicating the contribution of calcium transients to the rhythmic activity generated in leg motor neurons. In the stick insect deafferented preparation, after pilocarpine application brief patterns of coordinated activity among motor neuron pools supplying the three main leg joints may spontaneously occur (Büschges et al, 1995).…”
Section: Insect Walkingmentioning
confidence: 99%